FACTORS CAUSES OF STOCK OUT AND DRUG STAGNANT AT PHARMACY INSTALLATION OF HOSPITAL X MALANG - Tri Utami, Ni Nyoman Ayu; Ratri, Devita Rahmani; Nuthea, Merry (Jurnal Kedokteran Brawijaya)
Hospital pharmacy service is a supporting service as well as a revenue center in the hospital. More than 90% of hospital services use pharmaceutical supplies and 50% of hospital revenues come from managing pharmaceutical supplies. In the Covid-19 pandemic situation, the Pharmacy Installation must calculating the logistics management of the medicine properly. However, based on the hospitalization stock in May-July at X Hospital, there was still an incidence of stock out of 4.06% and stagnation of 2.44% due to poor drug procurement, which caused drug sales to decline. This study aims to analyze the factors that causing drug stock outs and stagnation in the Pharmacy Installation of X Hospital. This study uses a descriptive approach with data collection methods through observation, Focus Group Discussion (FGD), and a Likert scale questionnaire to get the root of the problem. Then the data was analyzed using the Fishbone Diagram and Pareto Diagram. The research subjects based on total sampling were all 11 staff of the Pharmacy Installation. The results obtained through the Fishbone Diagram are 13 root causes covering aspects of Man, Money, Method, Machine, Material, and Environment. The priority of the root cause of drug stock outs and stagnation in the Pharmacy Installation of X Hospital, namely HMIS is not optimal. Solutions that can be given are conducting intensive training for Pharmacy Installation staff in the use of HMIS, developing HMIS related to drug procurement, as well as repairing warehouse and pharmacy installation facilities and infrastructure.